We Will Tell You The Representation Of Family Communication In Today's Film: Analysis Of Semiotics Roland Barthes - Panggabean, Alya Hamzah; Simamora, Irma Yusriani (The Islamic Education and Multiculturalism Foundation, 2025)
Movies are one of the effective ways to represent the dynamics of family relationships. In addition to serving as entertainment, movies can also depict various social issues, one of which is family communication that is full of challenges. The purpose of the research was to analyze how family communication is represented in the film